The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4028/www.scientific.net/msf.717-720.343
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron X-Ray Topography Studies of the Propagation and Post-Growth Mutual Interaction of Threading Growth Dislocations with C-Component of Burgers Vector in PVT-Grown 4H-SiC

Abstract: Synchrotron White Beam X-ray Topography (SWBXT) imaging of wafers cut parallel to the growth axis from 4H-SiC boules grown using Physical Vapor Transport has enabled visualization of the evolution of the defect microstructure. Here we present observations of the propagation and post-growth mutual interaction of threading growth dislocations with c-component of Burgers vector. Detailed contrast extinction studies reveal the presence of two types of such dislocations: pure c-axis screw dislocations and those wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 9 publications
(7 reference statements)
0
14
0
Order By: Relevance
“…6) No correlations are found between the PL appearances of the TSDs and their Burgers vector directions (clockwise or counter-clockwise) of the screw component along the c-axis. Note that recent studies suggest the existences of mixed-type (c þ a) threading dislocations in 4H-SiC, [10][11][12] although both 1c and c þ a dislocations can be treated as TSDs in our X-ray topography analysis. In addition, TSDs exhibiting a PL appearance accompanying a short bright segment or a segment slightly extending along the step flow direction match the slightly enlarged defect topography contrast along the step flow direction.…”
Section: Resultsmentioning
confidence: 97%
“…6) No correlations are found between the PL appearances of the TSDs and their Burgers vector directions (clockwise or counter-clockwise) of the screw component along the c-axis. Note that recent studies suggest the existences of mixed-type (c þ a) threading dislocations in 4H-SiC, [10][11][12] although both 1c and c þ a dislocations can be treated as TSDs in our X-ray topography analysis. In addition, TSDs exhibiting a PL appearance accompanying a short bright segment or a segment slightly extending along the step flow direction match the slightly enlarged defect topography contrast along the step flow direction.…”
Section: Resultsmentioning
confidence: 97%
“…Similar wavy TSDs in PVT-grown 4H-SiC crystals were reported by Wu et al using synchrotron X-ray topography. 25) They observed TSDs showing curved, slightly wavy morphologies in the crystals, and suggested that they were helical TSDs resulting from the interaction of a nonequilibrium concentration of vacancies with TSDs. They also found that the attractive interaction between closely located two helical TSDs with opposite signs of Burgers vectors resulted in partial annihilation of the dislocation lines.…”
Section: Propagation Behaviors Of Pure and Mixedmentioning
confidence: 99%
“…4) However, 4H-SiC epitaxial layers (epilayers) still contain many dislocations such as threading screw dislocations (TSDs), threading edge dislocations (TEDs) and basal plane dislocations (BPDs), 5) which can degrade the performance of the devices. 6,7) To improve device performance and reliability, it is important to distinguish dislocation types [8][9][10][11][12][13][14][15][16][17][18][19][20] and investigate their electrical effects on devices. [21][22][23] The KOH etching method is widely used to determine the locations and kinds of dislocations in 4H-SiC epilayers.…”
Section: Hmentioning
confidence: 99%